2023
DOI: 10.3390/s23052644
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Changes Utilising Landsat Satellite Imageries for the Kumasi Metropolis and Its Adjoining Municipalities in Ghana (1986–2022)

Abstract: Forest loss, unbridled urbanisation, and the loss of arable lands have become contentious issues for the sustainable management of land. Landsat satellite images for 1986, 2003, 2013, and 2022, covering the Kumasi Metropolitan Assembly and its adjoining municipalities, were used to analyse the Land Use Land Cover (LULC) changes. The machine learning algorithm, Support Vector Machine (SVM), was used for the satellite image classification that led to the generation of the LULC maps. The Normalised Difference Veg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…For instance, [16] found that there were significant land use and land cover changes in the Kumasi Metropolis over a 30-year period, with negative effects on food crop production. Similarly, [17]observed an increase in residential land use in Kumasi and decreasing trends in forestlands and agricultural while [18]discovered an overall increase in built-up areas in the region.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, [16] found that there were significant land use and land cover changes in the Kumasi Metropolis over a 30-year period, with negative effects on food crop production. Similarly, [17]observed an increase in residential land use in Kumasi and decreasing trends in forestlands and agricultural while [18]discovered an overall increase in built-up areas in the region.…”
Section: Discussionmentioning
confidence: 98%
“…Studies of land cover changes, including the coverage of forested areas, are currently carried out mainly using data acquired by remote sensing methods, among which satellite imagery, e.g., Landsat, is very common [41][42][43]. Their high information abundance makes it possible to perform their own land cover classification and a range of analyses based on widely accepted indicators derived from them, e.g., NDVI [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…(1) Machine learning is a technical tool used for solving research problems. For example, satellite images were used to identify land use changes [5], crime was assessed through street images [6], COVID-19 plan distribution states for urban security risk assessment were identified [7,8], and remote sensing images were used to detect forest carbon stocks to predict their carbon sink development [9]. (2) Machine learning provides innovative perspectives on extracting design elements to facilitate decisions.…”
Section: Introductionmentioning
confidence: 99%